Understanding the gravity response variability of sedimentary basins using forward stratigraphic modelling. (December 2020) - Crombez, Vincent; Hauser, Juerg; Peeters, Luk; Chopping, Richard
Abstract: It is accepted that gravity inversions are non-unique and that multiple models will fit the data equally well. Over sedimentary basins, this implies that gravity anomalies can be equally well explained by sedimentary strata with constant densities over a highly heterogeneous basement, or by highly heterogeneous sedimentary strata over a constant density basement. While both scenarios minimise the difference between the predicted and observed gravity signal, neither are geologically plausible. In this work, we explore stratigraphic modelling as a new parameterisation for gravity models. By using a process-based numerical simulation to generate the sedimentary basins' density models we seek to focus only on geologically plausible models. We then study the variability of the sedimentary strata's gravity response (i.e. the range of possible geophysical signatures) to stratigraphic parameter changes. Results from a study of a 2D section in the Northern Carnarvon basin (the northwest shelf of Australia) emphasize that even when the stratigraphic models are trialled using a wide range of input parameters, the simulated gravity response still has a limited variability when compared to model results generated using other parameterisations. Lastly, our results provide insights into the global sensitivity of the gravity response, highlighting the sedimentary and stratigraphic parameters that most affect the geophysical signal, allowing for a discussion of the geologic and stratigraphic controls of the sedimentary basin's gravity response. Highlights: Stratigraphic modelling is used as a new parameterisation for gravity modelling. Gravity responses present a low variability when using this parameterisation. This parameterisation allows for the understanding of geologic controls on gravity response.